Estudo dos efeitos da pratica do Tai Chi Chuan sobre o estresse em professores de um Centro Unificado de Ensino da Prefeitura de São Paulo e de uma Instituição de Ensino Estadual de São Paulo - Kamigauti, Nilton (2016)
Currently, the high levels of stress pose a challenge to the contemporaneity. Teaching is one of the key professions of our society and which presents one of the highest levels of stress. In this work, it was observed that 65,3% of teachers from two schools of São Paulo suffer from stress. The purpose of this research was to assess the effects of Tai Chi Chuan on the level of stress of teachers. The instruments used were Lipp´s Stress Symptoms Inventory for Adults (ISSL) to measure the stress levels and, to the individuals that practiced Tai Chi Chuan, a questionnaire to evaluate the impressions of such individuals on practicing Tai Chi Chuan was also used. The proceeding for the selection of participants was, initially, to apply the ISSL on the 49 participating teachers. Out of such individuals, 32 presented stress and were divided, equally (based on their level of stress, age and time they have been teaching), into 16 on the control group and 16 on the experimental group. The 16 participants of the experimental group were ministered classes of Tai Chi Chuan (including Chi Kung and meditation); during the period of 2 months, they attended 8 classes of 1 hour each, once a week. At the end of the 2-month period, the 32 participants of the 2 groups were retested with ISSL and the questionnaire to evaluate the impressions of practicing Tai Chi Chuan was applied solely to the experimental group. As a result, we observed that the experimental group presented a decrease in the stress levels in order of 77,16%, while the control group did not present any relevant change. Tai Chi Chuan was proven to be an efficient technique for stress management, being a low cost activity, easily executed within the premises of the schools themselves and that does not require any equipment to be practiced; it presented a good acceptance, probably due to the swiftly achieved positive effects. Therefore, Tai Chi Chuan was effective in the decrease of the stress levels of the participating teachers